'You've seen us!': masculinities in the lives of boys with intellectual disability (ID) - Charnock, David (2013)
Access to the world of men can be closely guarded by non-disabled people and so disabled men can be persuaded to either conform, subvert or attempt to create an alternative masculine hegemony. For boys and men with Intellectual Disability (ID) little is known about their attempts to develop their gendered identities. This study aimed to explore whether boys with ID have ideas of what it means to be a boy, what influenced this and what ideas the boys had about their futures as men. Using an approach based on grounded theory, group and individual interviews were conducted with 21 boys in 7 groups from a special school engaged in plans about transition from school to the adult world. Using innovative methods including a sorting exercise and the boys own artwork, interviews were recorded and then transcribed. Analysis of the data revealed a developing construct of masculine identity established both outside and inside the interview room that could be identified as the way we do boy. The way we do boy is described in four themes: changes; ideals; experiences; vicariousness. Findings demonstrate that the four themes were instrumental in assisting the boys to think about their identities. However, the opportunities to practice their developing masculinity was limited and the boys talked about their struggles when their attempt to do this resulted in the uncovering of their difference and vulnerability. The analysis and discussion of this study develops into an explanatory theoretical framework for working with boys and men with ID about their masculinity. With the addition of Thomas’s (1999) work expressed as lenses, it is hoped this will provide a practical framework for use in services for both boys and men with ID.